An Experimental Study on Rotor Aerodynamic Noise Control Based on Active Flap Control - Zhiyuan Hu; Yang Liu; Yongjie Shi; Guohua Xu (Aerospace, 2023)
Reducing rotor aerodynamic noise is an important challenge in helicopter design. Active flap control (AFC) on rotors is an effective noise reduction method. It changes the segment airfoil shape, aerodynamic load distribution, and the wake path of the rotor flow by adding trailing edge flaps (TEFs). Although AFC noise reduction control is easily simulated, the relevant experiments have not been widely conducted due to test technical problems and limited financial support. The acoustic characteristics of the AFC-equipped rotor, such as the placement of TEFs for noise reduction and whether multiple winglets can provide a better effect than single winglets, have not been verified in previous experiments. In this work, an AFC-equipped rotor with two TEFs was designed, and its acoustic properties were tested in the FL-17 acoustic wind tunnel with microphone arrays in the far field. The results showed that the noise reduction effect of AFC was closely related to the control frequency and phase. Increasing the control phase could move the reduction region toward the azimuth-decreasing region for far-field noise. The noise reduction in a single outboard TEF was better than that in a single inboard TEF, while the dual-TEF model performed better. In this experiment, the average noise reduction in the observation point at the lower front of the rotor could be more than 3 dB, and the maximum noise reduction could be 6.2 dB.